Strategi Pengembangan dan Penilaian Kelayakan Wisata Edukasi Berkelanjutan Berbasis Perkebunan Kopi Rakyat, Gombengsari, Banyuwangi - Hendra Andiananta Pradana; Elida Novita; Nur Ika Dewi Wahyuni (JURNAL AGRIBISNIS TERPADU, 2026)
Coffee plantations in Gombengsari represent a potential natural resource that supports the development of sustainable educational tourism. Beyond their economic value, these plantations also provide informative value and a comprehensive cultural experience for tourists. This study aimed to determine management development strategies and assess the feasibility of educational tourism in Gombengsari Coffee Village based on its natural resource potential. A descriptive approach was employed to systematically described and explained the characteristics of the research object. The results showed that the development management strategy emphasizes financial management and transparency, enhancement and expansion of human resources, as well as appropriate monitoring and evaluation mechanisms. Based on the Global Sustainable Tourism Council (GSTC) assessment, the tourism site achieved a score of 57.1% of the total fulfilled sub-indicators. These findings indicate that the educational tourism initiative is feasible; however, improvements are still required for sub-criteria that are not yet fulfilled.